The State of Resting State Networks - Seitzman, Benjamin A. (Top Magn Reson Imaging, 2019)
OBJECTIVE: Functional MRI (fMRI) is currently used for pre-surgical planning, but is often limited to information on the motor and language systems. Resting state fMRI can provide more information on multiple other networks to the neurosurgeon and neuroradiologist, however, currently these networks are not well known among clinicians. The purpose of this manuscript is to provide an introduction to these networks for the clinician and to discuss how they could be used in the future for precise and individualized surgical planning. METHODS: We provide a short introduction to resting state fMRI and discuss multiple currently accepted resting state networks with a review of the literature. RESULTS: We review the characteristics and function of multiple somatosensory, association, and other networks. We discuss the concept of critical nodes in the brain and how the neurosurgeon can use this information to individually customize patient care. CONCLUSION: Although further research is necessary, future application of pre-surgical planning will require consideration of networks other than just motor and language in order to minimize post-surgical morbidity and customize patient care.